CALCIFIC AORTIC STENOSIS AND OSTEOPOROSIS: GENERAL MECHANISMS AND PERSPECTIVES OF PHARMACOLOGICAL CORRECTION - N. Yu. Karpova; M. A. Rashyd; N. A. Shostak; T. V. Kazakova (Klinicist)
The article discusses many common clinical and laboratory features of calcific aortic stenosis (CAS) and osteoporosis in patients of advanced age. After evaluation of bone mineral density, risk factors of fractures and falls, in conjunction with bone turnover markers, 2 distinct types of osteoporosis in CAS patients were described. The active character of bone’s turnover and aortic valve calcification can not regard CAS as degenerative, but regenerative process. The article is illustrated by case history, and elucidates the possibilities of pharmacological intervention, including new bisphosphonate drug – xydiphone.